2020
DOI: 10.1016/j.ceramint.2019.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carbonation on the low-temperature consolidation by Spark Plasma Sintering of carbonated calcium phosphate bioceramics

Abstract: Influence of carbonation on the low-temperature consolidation by SparkPlasma Sintering of carbonated calcium phosphate bioceramics. (2020) Ceramics International, 46 (5). 5799-5810.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…19 Moreover, the w CO 3 and the resulting Ca/P values due to CO 3 2− incorporation align closely with those documented in the literature, 19,51 confirming the feasibility of the FTIR-based quantification methodology for ACP NPs, as corroborated by elemental analysis (see Table S2, ESI†) and elsewhere. 52…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Moreover, the w CO 3 and the resulting Ca/P values due to CO 3 2− incorporation align closely with those documented in the literature, 19,51 confirming the feasibility of the FTIR-based quantification methodology for ACP NPs, as corroborated by elemental analysis (see Table S2, ESI†) and elsewhere. 52…”
Section: Resultsmentioning
confidence: 99%
“…19 Moreover, the wCO 3 and the resulting Ca/P values due to CO 3 2À incorporation align closely with those documented in the literature, 19,51 confirming the feasibility of the FTIR-based quantification methodology for ACP NPs, as corroborated by elemental analysis (see Table S2, ESI †) and elsewhere. 52 In the subsequent step, TGA was performed on all assynthesized NPs to quantify their structural water contents, wH 2 O(S). By examining the TGA curves and their first derivative (DTG), illustrated in Fig.…”
Section: àmentioning
confidence: 99%
“…As reported in Table 2 , the Ca/P ratio of HAp is 1.38 well below the stoichiometric Ca/P of 1.67, indicating a calcium-deficient apatite and supporting the hypothesis of a non-stoichiometric, multi-ion-substituted apatite with limited crystallinity. In some previous studies, Ortali et al [ 101 ] reported a Ca/P ratio of ~1.35 for a calcium-deficient HAp and of ~1.33 for a biomimetic nanocrystalline apatite, whereas Drouet et al [ 20 ] observed a gradual increase in the Ca/P ratio of nanocrystalline apatite from 1.30 to 1.48, depending on the maturation time, which was up to 20 days. The Ca/P ratio in the composites further decreases to 1.26 for HAp10Chit and to 1.27 for HAp10ChitSrRAN.…”
Section: Resultsmentioning
confidence: 99%
“…The non-stoichiometry of the produced apatite powder was further investigated by peak decomposition of the ν 4 PO 4 (800–400 cm −1 ) and ν 2 CO 3 (900–800 cm −1 ) infrared spectral domains. Indeed, in the case of biomimetic apatite, these spectral domains are characterised by the presence of apatitic and non-apatitic phosphate and carbonate environments [ 21 , 74 , 84 , 101 ]: the apatitic ones include ions in the apatite normal crystallographic sites, while the non-apatitic ions are not located within the apatite lattice [ 20 ]. As a matter of fact, the non-apatitic (or labile) environments in bone-like apatite are associated with a thin hydrated layer surrounding the nanocrystals, where exchangeable ions (mostly divalent Ca 2+ , HPO 4 2− and CO 3 2− ) are present [ 21 , 74 , 84 , 101 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation